Recent abacavir use and incident cardiovascular disease in contemporary-treated people with HIV. (1st March 2023) - Jaschinski, Nadine; Greenberg, Lauren; Neesgaard, Bastian; Miró, Jose M.; Grabmeier-Pfistershammer, Katharina; Wandeler, Gilles; Smith, Colette; De Wit, Stéphane; Wit, Ferdinand; Pelchen-Matthews, Annegret; Mussini, Cristina; Castagna, Antonella; et al.
Abstract : Objective: Assessing whether the previously reported association between abacavir (ABC) and cardiovascular disease (CVD) remained amongst contemporarily treated people with HIV. Design: Multinational cohort collaboration. Methods: RESPOND participants were followed from the latest of 1 January 2012 or cohort enrolment until the first of a CVD event (myocardial infarction, stroke, invasive cardiovascular procedure), last follow-up or 31 December 2019. Logistic regression examined the odds of starting ABC by 5-year CVD or chronic kidney disease (CKD) D:A:D risk score. We assessed associations between recent ABC use (use within the past 6 months) and risk of CVD with negative binomial regression models, adjusted for potential confounders. Results: Of 29 340 individuals, 34% recently used ABC. Compared with those at low estimated CVD and CKD risks, the odds of starting ABC were significantly higher among individuals at high CKD risk [odds ratio 1.12 (95% confidence interval = 1.04–1.21)] and significantly lower for individuals at moderate, high or very high CVD risk [0.80 (0.72–0.88), 0.75 (0.64–0.87), 0.71 (0.56–0.90), respectively]. During 6.2 years of median follow-up (interquartile range; 3.87–7.52), there were 748 CVD events (incidence rate 4.7 of 1000 persons-years of follow up (4.3–5.0)]. The adjusted CVD incidence rate ratio was higher for individuals with recent ABC use [1.40 (1.20–1.64)] compared with individuals without, consistent across sensitivity analyses. The association did not differ according to estimated CVD (interaction P = 0.56) or CKD ( P = 0.98) risk strata. Conclusion: Within RESPOND's contemporarily treated population, a significant association between CVD incidence and recent ABC use was confirmed and not explained by preferential ABC use in individuals at increased CVD or CKD risk.